MANAJEMEN PENDIDIKAN INKLUSI DI SEKOLAH DASAR NEGERI 32 KOTA BANDA ACEH - Ery Wati (Center for Research and Publication Universitas Islam Negeri (UIN) of Ar-Raniry, 2014)
The inclusive program of the State Primary School 32 Banda Aceh will be successful if it is supported by human resources professionally in carrying out school operational. This study aims at knowing the inclusive education program, inclusive educational implementation management and the encountered obstacles in the implementation of inclusive education management at SD Negeri 32 Banda Aceh. This research uses descriptive qualitative method. The techniques of collecting data were observations, interviews, and documentations. The subject of the research were school head master, vice of school head master, class teacher supervisor, special teacher assistant, and parents. The results of the research shows that 1) The school head master program in implementing inclusive education is through conducting training delivery to the teachers, accepting the students ABK, modifying curriculum and affording school infrastructure in accordance with the needs of the students. 2) The implementation of inclusive education management can be seen from the number of students with special needs in academic year 2009/2010 that out of 19 students possessing one special teacher assistant, the curriculum being modified based on the students need. 3) The constraints of inclusive education programs are education funding, insufficient facilities and infrastructure, and lack of teacher special assistants.